Vitreous Mediators in Retinal Hypoxic Diseases - Roberto dell'Omo; Francesco Semeraro; Giulio Bamonte; Francesco Cifariello; Mario R. Romano; Ciro Costagliola (Mediators of Inflammation)
The causes of retinal hypoxia are many and varied. Under hypoxic conditions, a variety of soluble factors are secreted into the vitreous cavity including growth factors, cytokines, and chemokines. Cytokines, which usually serve as signals between neighboring cells, are involved in essentially every important biological process, including cell proliferation, inflammation, immunity, migration, fibrosis, tissue repair, and angiogenesis. Cytokines and chemokines are multifunctional mediators that can direct the recruitment of leukocytes to sites of inflammation, promote the process, enhance immune responses, and promote stem cell survival, development, and homeostasis. The modern particle-based flow cytometric analysis is more direct, stable and sensitive than the colorimetric readout of the conventional ELISA but, similar to ELISA, is influenced by vitreous hemorrhage, disruption of the blood-retina barrier, and high serum levels of a specific protein. Finding patterns in the expression of inflammatory cytokines specific to a particular disease can substantially contribute to the understanding of its basic mechanism and to the development of a targeted therapy.